Professor Zdzisław Kołaczkowski (1910-1985) - Marecki, Bogusław (Anthropological Review, 1985)
Professor Zdzisław Kołaczkowski died on the 6th of June 1985 in the age of 75 years. Since 1965 until the end of his life he was the Head of the Department of Functional Anatomy, Academy of Physical Education in Poznań. In his research work he was interested in the human muscle system. Mainly in the prenatal period. He was the author of anatomy textbooks.